EFEKTIVITAS KEGEL EXERCISE TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU SETELAH MELAHIRKAN - Susi Hartati; Yesi Arisonaidah; Nelfi Sarlis (Ensiklopedia of Journal, 2023)
The incidence of new mothers who experienced perineal injuries at the age of 25-30 years was 24 percent and at the age of 32-39 years was 62 percent. Perineal wound care is not optimal can turn into infection, infection after childbirth causes maternal death after childbirth. This study was to determine the effectiveness of Kegel Exercise on perineal wound healing in mothers after giving birth at PMB Ernita in 2022. This type of research is quantitative while the retrospective design is considering case and control groups based on their occurrence. Research activities in September 2021-May 2022. The population is 21 people with 1st and 2nd degree injuries, the sample is 20 people with consecutive sample technique. Univariate and bivariate data analysis. Univariate results 10 people who were not given kegel exercise obtained the majority of perineal wounds in the category of not yet healed amounting to 8 people (80%) and 10 people who were given kegel exercise the majority of perineal wounds in the healed category amounting to 9 people (90%). The results of the MannWhitney test show that the p-value < is 0.000 <0.05, meaning that Ho is rejected. Ha is accepted. It is hoped that PMB can provide counseling to pregnant women with perineal injuries to use Kegel exercises for healing perineal wounds.Keywords: Kegel Exercise, Perineal Wound